Strategies to Renew Federal Facilities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The United States real property portfolio is critical infrastructure that provides places and means for the federal government to operate and generate the products, services, security, and assurances that contribute to national prosperity and values. This report identifies broad-based, practical, and compelling strategies for securing continuing investment in the renewal of federal real properties and portfolios. Strategies to Renew Federal Facilities focuses on the how- not the what - for adapting, repurposing, restoring, recapitalizing, and replacing real property assets.
Keywords: Engineering and Technology

Extraordinary Engineering Impacts on Society: Proceedings of a Symposium - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On August 18-19, 2022, the National Academy of Engineering (NAE) held a symposium to explore how support of fundamental engineering and engineering education research by the National Science Foundation (NSF) has led to positive societal and economic impacts. The symposium - which was sponsored by the NSF Directorate for Engineering - was held to provide input to the NAE Committee on Extraordinary Engineering Impacts on Society as part of a larger effort to develop clear, compelling narratives for the public about the sources and effects of engineering innovations. Speakers at the symposium shared their personal stories and provided insights on how engineers influence not only technology and the national infrastructure but the economy, population health, manufacturing, disaster resilience, and many other aspects of daily life. This publication summarizes the presentations and discussion of the symposium.
Keywords: Engineering and Technology

Enhancing Urban Sustainability Infrastructure: Mathematical Approaches for Optimizing Investments: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Board on Mathematical Sciences and Analytics and Board on Infrastructure and the Constructed Environment convened a 3-day public workshop on July 13, 20, and 27, 2022, to explore state-of-the-art analytical tools that could advance urban sustainability through improved prioritization of public works projects. Invited speakers included people working in urban sustainability, city planning, local public and private infrastructure, asset management, and infrastructure investment; city officials and utility officials; and statisticians, data scientists, mathematicians, economists, computer scientists, and artificial intelligence/machine learning experts. Presentations and workshop discussions provided insights into new research areas that have the potential to advance urban sustainability in public works planning, as well as the barriers to their adoption. This publication summarizes the presentation and discussion of the workshop.
Keywords: Engineering and Technology; Environment and Environmental Studies

Corrosion of Buried Steel at New and In-Service Infrastructure - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Steel is a common component of U.S. infrastructure, but that steel can corrode when buried in soil, rock, or fill. Steel corrosion is estimated to cost the United States 3-4 percent of its gross domestic product every year, and it can lead to infrastructure failure, loss of lives, property, disruption of energy and transportation systems, and damage to the environment. Although the mechanisms of steel corrosion are well understood, limited data on subsurface corrosion and the inability to measure corrosivity directly make accurate corrosion prediction through modeling a challenge. When hazardous levels of corrosion does occur, it is difficult to determine whether the cause was related to site selection, engineering decisions, changes in subsurface conditions, or a combination of these factors. This report explores the state of knowledge and technical issues regarding the corrosion of steel used for earth applications (e.g., for ground stabilization, pipelines, and infrastructure foundations) in unconsolidated earth or rock in different geologic settings. The report summarizes mechanisms of steel corrosion, assesses the state of practice for characterizing factors in the subsurface environment that influence corrosion and corrosion rates, and assesses the efficacy and uncertainties associated with quantitative, field, and laboratory methods for predicting corrosion. The industries and experts most involved with managing buried steel should collaborate to improve multidisciplinary understanding of the processes that drive buried steel corrosion. Developing a common lexicon related to buried steel corrosion, generating new data on corrosion through collaborative long-term experiments, sharing and managing data, and developing new data analytical techniques to inform infrastructure design, construction, and management decisions are key. Industries, experts, and regulators should collaboratively develop decision support systems that guide site characterization and help manage risk. These systems and new data should undergird a common clearinghouse for data on corrosion of buried steel, which will ultimately inform better and more efficient management of buried steel infrastructure, and protect safety and the environment.
Keywords: Engineering and Technology; Earth Sciences

Transforming EPA Science to Meet Today's and Tomorrow's Challenges - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Since its establishment in 1970, the mission of the Environmental Protection Agency is to protect human health and the environment. EPA develops regulations, ensures compliance, and issues policies, in coordination with state, tribal, and local governments. To accomplish its mission, EPA should be equipped to produce and access the highest quality and most advanced science. The Office of Research and Development (ORD) provides the scientific bases for regulatory and public health policies that have broad impacts on the nation’s natural resources and quality of human life, and that yield economic benefits and incur compliance costs for the regulated community. In addition, ORD develops the agency core research capabilities, providing tools and methods for meeting current and anticipating future environmental challenges, such as the risks to health and the environment posed by climate change. Because challenges associated with environmental protection today are complex and affected by many interacting factors, the report points to the need for a substantially broader and better integrated approach to environmental protection. This report calls for EPA ORD to pursue all of its scientific aims in a new framework—to apply systems thinking to a One Environment − One Health approach in all aspects of ORD work. To accomplish this, the report provides actionable recommendations on how ORD might consider incorporating emerging science and systems thinking into the agency research planning, so that ORD can become an increasingly impactful organization. The report identifies a number of high-priority recommendations for ORD to pursue in taking advantage of a broad range of advanced tools, in concert with collaborators in other federal agencies and the broader scientific community. Given the resource constraints, the report recognizes that ORD will have to make decisions about priorities for implementing its recommendations, and that ORD leadership is in the best position to set those priorities as implementation begins. The report concluded by stating that shifting to a systems-thinking approach will require renewed support from science leadership, enhanced strategic planning, investment in new and broader expertise and tools, and a reimagined and inclusive commitment to communication and collaboration.
Keywords: Environment and Environmental Studies; Engineering and Technology

An Assessment of the Material Measurement Laboratory at the National Institute of Standards and Technology: Fiscal Year 2023 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Since 1959, the National Institute of Standards and Technology (NIST) has annually engaged the National Academies of Sciences, Engineering, and Medicine to assemble panels of experts to assess the quality and effectiveness of the NIST measurements and standards laboratories as well as the adequacy of the laboratory resources. This report assesses the Material Measurement Laboratory (MML), with a focus on technical programs, quality of research, scientific and technical expertise, dissemination products and strategies, and how well budget, facilities, equipment, and human resources support technical programs and MML objectives.
Keywords: Engineering and Technology